1366. In Vitro and In Vivo Activity of Cefiderocol against Stenotrophomonas maltophilia Clinical Isolates. (26th November 2018) - Ito, Akinobu; Ota, Merime; Nakamura, Rio; Tsuji, Masakatsu; Sato, Takafumi; Yamano, Yoshinori
Abstract: Background: Cefiderocol (S-649266, CFDC) is a novel siderophore cephalosporin against Gram-negatives, including carbapenem (CR)-resistant strains. Its spectrum includes both the Enterobacteriaceae but also nonfermenters, including Stenotrophomonas maltophilia —an opportunistic pathogen with intrinsic resistance to carbapenem antibiotics. In this study, in vitro activity and in vivo efficacy of CFDC and comparators against S. maltophilia were determined. Methods: MICs of CFDC and comparators (trimethoprim/sulfamethoxazole (TMP/SMX), minocycline (MINO), tigecycline (TGC), ciprofloxacin (CPFX), cefepime (CFPM), meropenem (MEPM), and colistin (CL)) were determined by broth microdilution method as recommended by CLSI. The MIC against CFDC was determined using iron-depleted cation-adjusted Mueller–Hinton broth. In vivo efficacy of CFDC, CFPM, ceftazidime–avibactam (CAZ/AVI), MEPM, and CL was evaluated using neutropenic murine systemic infection model caused by strain SR21970. The 50% effective doses (ED50 s) were calculated by the logit method using the survival number at each dose 7 days after infection. Results: MIC90 of CFDC and comparators against the 216 clinical isolates from global countries collected in SIDERO-CR 2014/2016 study are shown in the table. CFDC, TMP/SMX, MINO, and TGC showed good activity with MIC90 of 0.5, 0.25/4.75, 1, and 2 µg/mL, respectively. CFDC, MINO, and TGC inhibited growth of all tested strains at ≤1, ≤4, and ≤8 µg/mL although two strains showed resistance to TMP/SMX. MICs of CFPM, CAZ/AVI, MEPM, and CL were ≥32 µg/mL. The ED50 of CFDC against S. maltophilia SR21970 with MIC of 0.125 mg/mL was 1.17 mg/kg/dose. Conversely, MICs of CFPM, CAZ/AVI, MEPM/CS, and CL against SR21970 were 32 μg/mL or higher, and ED50 s were >100 mg/kg/dose, showing that CFDC had potent in vivo efficacy against S. maltophilia strain which was resistant to other antibiotics. Conclusion: CFDC showed potent in vitro activity against S. maltophilia, including TMP/SMX-resistant isolates. CFDC also showed potent in vivo efficacy reflecting in vitro activity against S. maltophilia in murine systemic infection model. Disclosures: A. Ito, Shionogi & Co., Ltd.: Employee, Salary. M. Ota, Shionogi & Co., Ltd.: Employee, Salary. R. Nakamura, Shionogi & Co., Ltd.: Employee, Salary. M. Tsuji, Shionogi & Co., Ltd.: Employee, Salary. T. Sato, Shionogi & Co., Ltd.: Employee, Salary. Y. Yamano, Shionogi & Co., Ltd.: Employee, Salary.